Recombinant Thrombomodulin Suppresses Histone-Induced Neutrophil Extracellular Trap Formation - Shrestha, Binita; Ito, Takashi; Kakuuchi, Midori; Totoki, Takaaki; Nagasato, Tomoka; Yamamoto, Mika; Maruyama, Ikuro (Frontiers in Immunology, 2019)
Histones, the major protein components of chromatin, are released into the extracellular space during sepsis, trauma, and ischemia-reperfusion injury, and subsequently mediate organ failure. Extracellular histones can promote endothelial damage and platelet aggregation, which can be suppressed by administration of recombinant thrombomodulin (rTM). The present study aimed to clarify whether histones can activate neutrophils to induce NET formation and whether rTM can prevent histone-induced NET formation. NET formation was analyzed in vitro by stimulating human neutrophils with histones in the absence or presence of rTM. NET formation was further analyzed in vivo by intravenous infusion of histones into rats with or without rTM. Histones induced NET release in a dose-dependent manner in vitro and NET release was induced as early as 1 h after stimulation. Histone-induced NET release was independent of NADPH oxidase. rTM suppressed histone-induced NET release in vitro as well as in vivo. The suppression might be mediated by rTM binding to histones, as suggested by analysis using a quartz crystal microbalance system. The present findings suggest that histones can activate neutrophils to form NETs and that rTM can inhibit histone-induced NET formation.